DESKRIPSI KECEMASAN MATEMATIKA SISWA DITINJAU DARI KEMAMPUAN PEMAHAMAN MATEMATIKA SISWA SMP - Meta Trisna Wati; M. Imamuddin; Elvi Julfitri (KOLONI, 2022)
This study aims to provide an overview of students' math anxiety in terms of junior high school students' mathematical understanding abilities. The population in this study were all students of class VII at a private junior high school in Bukittinggi for the 2022/2023 academic year. By using a questionnaire instrument and interviews from several students, one class was selected with a total of 12 students. This research is a qualitative descriptive research with descriptive method. Data were obtained through instruments in the form of a questionnaire with indicators of mathematical anxiety as many as 10 statement items, analyzed in the form of descriptive statistics which were then categorized based on 4 category norms, including always, often, sometimes, and never. The results of this study are according to the data generated in the high category there are 2 students with math anxiety 17% of students, in the medium category there are 6 students with math anxiety 50% of students, and in the low category there are 4 students with math anxiety category 33% of students. It can be seen that there are more categories of moderate math anxiety than high or low math anxiety categories. So from the results of the data obtained according to the questionnaire given to class VII students, students' math anxiety is in the medium category. So that in this study the results of anxiety can also cause a positive influence from within students so that students' understanding abilities can increase if anxiety has control from within students and there is assistance from the teacher in generating motivation from within students. Keywords: anxiety, ability to understand mathematics